1999
DOI: 10.1159/000051374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Retinoids on Vascular Endothelial Growth Factor Production by Cultured Human Skin Keratinocytes

Abstract: Background: Vascular endothelial growth factor (VEGF), a potent angiogenic factor and vasodilator, is strongly expressed by epidermal keratinocytes in many angiogenesis-dependent skin disorders. Retinoids may modulate VEGF in skin and this may be related to an effect on rosacea. Aim: To investigate the effect of retinaldehyde on VEGF production by human keratinocytes. Methods: The effects of different concentrations of retinoids (all-trans-retinal and all-trans-retinoic acid) on VEGF production by cultured hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…Vasodilators such as VEGF are expressed in epidermal KCs [5] and thus may be contributing factors for rosacea. IL-1 ␣ induces angiogenesis by activating VEGF signaling between infl ammatory and endothelial cells [11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasodilators such as VEGF are expressed in epidermal KCs [5] and thus may be contributing factors for rosacea. IL-1 ␣ induces angiogenesis by activating VEGF signaling between infl ammatory and endothelial cells [11] .…”
Section: Discussionmentioning
confidence: 99%
“…M has recently been shown to enhance the chemically (2,4,6-trinitrobenzene sulfonic acid sodium salt, TNBS) induced production and gene expression of IL-1 ␣ through activation of nuclear factor B and activator protein 1 following hapten application in murine epidermal Pam cells [4] . IL-1 ␣ may induce angiogenesis by activating VEGF (vascular endothelial growth factor) [5] expressed in KCs via interactions of infl ammatory cells with endothelial cells. Thus, IL-1 ␣ would appear related to the onset of rosacea [6] , a disorder characterized by persistent erythemas and dilated blood vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAL has revealed a retinoid-like activity in the stimulation of proliferation and differentiation, comedolysis, inhibition of protein expression (in particular melanin) and increase in epidermal thickness [24,26,27]. RAL also shows a specific antibacterial activity against Propionibacterium acnes [28,29].…”
Section: Retinaldehydementioning
confidence: 99%
“…The decrease in vascular endothelial growth factor (VEGF) expression by keratinocytes on contact with retinal has been recently published, and the conclusions showed that the decrease in VEGF expression may prevent skin neoangiogenesis in certain skin diseases [18]. We recently reported on the syntheses of 9-methylene-and 13-methyleneretinals 1 ) [19].…”
mentioning
confidence: 99%